1996
DOI: 10.1021/ac960472p
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Signal Suppression by Anionic Surfactants in Capillary Electrophoresis−Electrospray Ionization Mass Spectrometry

Abstract: Micellar-mediated capillary electrophoresis (CE) is used for a wide variety of applications, including the separation of pharmaceuticals, environmental contaminants, illicit drugs, DNA fragments, and many other biological samples. The electrospray ionization interface is one of the most common CE-MS interfaces. Coupling micellar-mediated CE separations with MS detection combines two very powerful, widely applicable analytical techniques. Some types of surfactants strongly interfere with electrospray ionization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
145
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(146 citation statements)
references
References 48 publications
1
145
0
Order By: Relevance
“…In sharp contrast to these APCI results, the efficiency of ESI is known to decrease significantly in the presence of nonvolatile constituents such as sodium phosphate [2,8]. SDS, which is often employed as a pseudo-stationary phase in micellar electrokinetic chromatography (MEKC), is an even stronger ion suppressor in ESI [18,19]. However, the infusion experiments indicated that the addition of 20 mM SDS did not result in reduced signal intensities in APCI-MS. For hydrocortisone, SDS even caused a slight signal increase.…”
Section: Bge Compositionmentioning
confidence: 99%
“…In sharp contrast to these APCI results, the efficiency of ESI is known to decrease significantly in the presence of nonvolatile constituents such as sodium phosphate [2,8]. SDS, which is often employed as a pseudo-stationary phase in micellar electrokinetic chromatography (MEKC), is an even stronger ion suppressor in ESI [18,19]. However, the infusion experiments indicated that the addition of 20 mM SDS did not result in reduced signal intensities in APCI-MS. For hydrocortisone, SDS even caused a slight signal increase.…”
Section: Bge Compositionmentioning
confidence: 99%
“…Indeed, common buffers used in CE-UV such as phosphate or borate which provide good peak shapes and thus high separation efficiency are nonvolatile and/or can contain modifiers such as CD, SDS, and so on. These additives are not suitable or even detrimental for on-line CE-ESI/MS since they may contaminate the MS ionization chamber and cause significant ion suppression [18,19]. Numerous solutions have been proposed to overcome these difficulties, such as the partial filling approach in chiral analysis [20], but they are not always well adapted or easy to carry out.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, secondary structure elements and structural dynamics can also be studied by mass spectrometry in hydrogen/deuterium exchange experiments, in which the exchange kinetics of amide protons are measured (21-23), making ES mass spectrometry an attractive tool for studies of protein structure and organization. However, the study of detergent-solubilized proteins by ES mass spectrometry is challenging because of protein ion signal suppression due to the presence of excess detergent (24). Consequently, analysis of integral membrane proteins has usually relied on the removal of detergent prior to sample analysis by, for example, organic solvent extraction (25) or reversed-phase (26) or size-exclusion (27,28) chromatography.…”
mentioning
confidence: 99%